Optically clear, oil-resistant adhesive
An optically clear adhesive composition with specific monomers and a photoinitiator addresses the issue of oil-induced swelling and contamination in electronic displays, ensuring durability and optical clarity by resisting delamination and yellow edge defects.
Patent Information
- Application Number
- JP2021566442
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-10
- Filing Date
- 2020-05-05
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2040-05-05
AI Technical Summary
Optically clear adhesives (OCAs) used in electronic displays are susceptible to swelling and contamination from oils, leading to mechanical and optical failures such as delamination and yellow edge defects, which current edge sealing methods like foam tape or liquid adhesives fail to prevent effectively.
An optically clear adhesive composition comprising hydroxyalkyl (meth)acrylates with 2-4 carbon alkyl groups, short alkyl (meth)acrylates with 6 or fewer carbon groups, and a photoinitiator, which provides oil resistance and maintains optical clarity and bond strength, minimizing swelling and delamination.
The adhesive composition exhibits high oil resistance, maintaining optical clarity, bond strength, and preventing mechanical failures by minimizing swelling and delamination, even when exposed to oils like sebum and household oils.
Smart Images

Figure 0007618584000001 
Figure 0007618584000002 
Figure 0007618584000003
Abstract
Description
[Technical field]
[0001] The present invention relates generally to the field of optically clear adhesives. In particular, the present invention is an optically clear, oil-resistant adhesive composition. [Background technology]
[0002] Optically clear adhesives (OCAs) are currently used in a variety of electronic display applications and play a critical role in display performance. The primary function of OCAs is to improve optical quality by eliminating air gaps between the multi-component layers of a display assembly. The presence of interlayer air gaps can result in light reflections and thus unintentionally reduce the brightness and contrast of the display. Many of the material requirements for OCAs are very challenging given the ever-evolving nature of display technology combined with rapidly changing component layers and features. OCAs are not only required to form good adhesive bonds with the numerous substrates that make up adjacent layers in the assembly, but they also need to have excellent compatibility with all of the various relief features of the assembly.
[0003] Many electronic devices, such as mobile phones and wearable devices, need to be durable enough to withstand a variety of conditions. When various chemicals and substances come into contact with OCA, they can swell the OCA and eventually cause failure, either mechanically or optically. Examples of mechanical failures can include peeling / delamination, or the presence of air bubbles. Examples of optical failures can include yellow edge mura defects. These failures can result from exposure and contact of OCA with oils. In particular, contact with sebum, which includes triglycerides, wax esters, squalene, and free fatty acids and is said to be secreted from sebaceous glands found in human skin, can contribute to failure of OCA. Thus, OCA can become contaminated with oils secreted by human skin, causing failure of OCA over time.
[0004] After all the components of the display assembly are integrated using the OCA, an edge sealing tape, typically in the form of a foam tape or liquid adhesive, is applied around the edges of the display assembly. However, foam tape is not an effective way to seal against chemical intrusion, and as a result, the OCA can be contaminated by chemicals such as human skin oils, sunscreens, and household oils such as cooking oils. When the liquid adhesive is applied to the edges of the display assembly, the OCA is initially in direct contact with the liquid adhesive. However, the composition of commonly used liquid adhesives typically includes about 40% to 75% by weight of polyurethane acrylate, acrylate monomers, photoinitiators, and other additives. When in contact with the liquid adhesive, the OCA may swell, resulting in a white or yellow edge after UV curing of the liquid adhesive.
[0005] Therefore, it would be desirable to have an optically clear adhesive with oil resistant properties to prevent the above potential problems. Summary of the Invention
[0006] In one embodiment, the invention is an oil-resistant adhesive composition comprising a hydroxyalkyl (meth)acrylate having an alkyl group containing 2-4 carbons, a short alkyl (meth)acrylate having an alkyl group containing 6 or less carbons, and a photoinitiator. After the adhesive composition is immersed in oleic acid at room temperature for 7 days, the adhesive composition has a swelling percentage of less than about 10%.
[0007] In another embodiment, the invention is an oil-resistant adhesive composition comprising a hydroxyalkyl (meth)acrylate having an alkyl group containing 2-4 carbons, a short alkyl (meth)acrylate having an alkyl group containing 6 or less carbons, and a photoinitiator. The oil-resistant adhesive composition has a haze of less than about 5% after being immersed in oleic acid at room temperature and placed in an oven at 70°C for 4 hours, then removed from the oleic acid and allowed to stand for about 5 minutes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present invention is an oil-resistant optically clear adhesive (OCA) composition. The OCA composition is resistant to oils such as human body oils, household oils, sunscreen oils, UV-curable liquid adhesives, etc. The oil-resistant OCA is useful for improving the durability of mobile devices (i.e., phones, wearable devices, notebooks, etc.) and protecting electronic devices from chemical ingress or contamination that may cause mechanical and / or optical failures. Examples of failures include air bubbles, reduced adhesion, and optical unevenness due to swelling of adhesives used in electronic devices. Thus, the oil-resistant OCA of the present invention is suitable for direct bonding applications for electronic assemblies and does not require edge protection to prevent contact with oil. In addition to exhibiting resistance to oil, the OCA of the present invention also has a low glass transition temperature (Tg), effective adhesion, and optical clarity.
[0009] The optically clear oil-resistant adhesive composition of the present invention generally comprises a primary monomer, a secondary monomer, and optionally a chain transfer agent. The primary monomer generally functions to provide adhesion in addition to oil resistance. The primary monomer is a hydroxyalkyl (meth)acrylate in which the alkyl group contains 2-4 carbons. These can be primary or secondary hydroxy groups. In one embodiment, the primary monomer is a hydroxyalkyl acrylate in which the alkyl group contains 2-4 carbons. Examples of suitable primary monomers include, but are not limited to, 4-hydroxybutyl acrylate (4-HBA) and 2-hydroxyethyl acrylate (2-HEA). In one embodiment, the oil-resistant OCA composition comprises about 35 to about 80% by weight of the primary monomer (or once polymerized polymer), particularly about 40 to about 70% by weight of the primary monomer, more particularly about 45 to about 60% by weight of the primary monomer.
[0010] The secondary monomer generally functions to provide adhesion and can also help modify the glass transition temperature and molecular weight of the oil-resistant OCA. In some applications, molecular weight can be important because a lower molecular weight can typically improve the flow of the adhesive (high tan δ), which can be important for applications that require a wet ink step. Flow can also be related to the glass transition temperature of the adhesive. The secondary monomer is a short alkyl (meth)acrylate, where the alkyl group contains 6 or fewer carbons. Examples of suitable secondary monomers include, but are not limited to, n-hexyl acrylate, n-butyl acrylate, cyclohexyl methacrylate (CHMA), cyclohexyl acrylate (CHA), 2-methylbutyl acrylate, and hydroxypropyl methacrylate. In one embodiment, the oil-resistant OCA composition comprises about 20 to about 60% by weight of the secondary monomer, particularly about 30 to about 60% by weight of the secondary monomer, and more particularly about 40 to about 55% by weight of the secondary monomer.
[0011] Other monomers may also be included in the oil-resistant OCA for various purposes. Examples of suitable monomers include, but are not limited to, 2-ethoxyethoxyethyl acrylate (2-EHA), acrylamide, 2-cyanoethyl acrylate, and tetrahydrofurfuryl acrylate (THFA).
[0012] The oil-resistant OCA also includes a photoinitiator for polymerizing the primary and secondary monomers. Some exemplary photoinitiators are benzoin ethers (e.g., benzoin methyl ether or benzoin isopropyl ether), or substituted benzoin ethers (e.g., anisoin methyl ether). Other exemplary photoinitiators are substituted acetophenones, such as 2,2-diethoxyacetophenone, or 2,2-dimethoxy-2-phenylacetophenone (commercially available under the trade name IRGACURE 651 from BASF Corp., Florham Park, NJ, USA, or under the trade name ESACURE KB-1 from Sartomer, Exton, PA, USA). Still other exemplary photoinitiators are substituted alpha-ketols, such as 2-methyl-2-hydroxypropiophenone, aromatic sulfonyl chlorides, such as 2-naphthalenesulfonyl chloride, and photoactive oximes, such as 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime. Other suitable photoinitiators include, for example, 1-hydroxycyclohexyl phenyl ketone (commercially available under the trade name IRGACURE 184), bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (commercially available under the trade name IRGACURE 819), 2,4,6-trimethylbenzoylphenylphosphinic acid ethyl ester (IRGACURE TPO-L), 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one (commercially available under the trade name IRGACURE 2959), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone (commercially available under the trade name IRGACURE 369), 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one (IRGAC ... 907), and 2-hydroxy-2-methyl-1-phenylpropan-1-one (available under the trade name DAROCUR 1173 from Ciba Specialty Chemicals Corp., Tarrytown, NY, USA).In one embodiment, the oil-resistant OCA composition comprises from about 0.01 to about 2 wt. % photoinitiator, specifically from about 0.02 to about 1 wt. % photoinitiator, and more specifically from about 0.02 to about 0.5 wt. % photoinitiator.
[0013] The oil-resistant OCA may optionally contain a chain transfer agent to control polymer molecular weight and rheology and provide high flow properties. Examples of useful chain transfer agents include, but are not limited to, carbon tetrabromide, alcohols (e.g., ethanol and isopropanol), mercaptans, or thiols (e.g., lauryl mercaptan, butyl mercaptan, tert-dodecyl mercaptan, ethanethiol, isooctyl thioglycolate, 2-ethylhexyl thioglycolate, 2-ethylhexyl mercaptopropionate, ethylene glycol bisthioglycolate), mercaptopropane trimethoxysilane, 1,4-bis(3-mercaptobutyloxy)butane, and mixtures thereof. Examples of particularly suitable chain transfer agents include 3-mercaptopropyl trimethoxysilane. In one embodiment, the oil-resistant OCA includes up to about 0.5 wt. % chain transfer agent, specifically from about 0.05 to about 0.4 wt. % chain transfer agent, and more specifically from about 0.1 to about 0.25 wt. % chain transfer agent.
[0014] Other materials may be added to the oil-resistant OCA for special purposes, including, for example, molecular weight control agents, coupling agents, plasticizers, heat stabilizers, adhesion promoters, UV stabilizers, UV absorbers, curing agents, polymer additives, photoinitiators, crosslinking agents, surface modifiers, UV light stabilizers, antioxidants, antistatic agents, thickeners, fillers, thixotropic agents, processing aids, nanoparticles, and combinations thereof.
[0015] To make the oil-resistant OCA of the present invention, the primary monomer, secondary monomer, photoinitiator, optional chain transfer agent, and other optional materials are mixed and partially polymerized by exposure to ultraviolet (UV) light to form a coatable syrup. In one embodiment, the materials are exposed to UV light in a nitrogen atmosphere. In one embodiment, the syrup has a viscosity of about 1000 cp. Additional photoinitiator is added to the syrup, and the syrup can be mixed with a roller. The resulting syrup is degassed and coated onto a substrate. In one embodiment, the syrup is knife coated between two siliconized release liners at a thickness of 150 microns. The resulting coating is then cured by exposure to low intensity UV light to obtain complete conversion. In one embodiment, the coating is exposed to UV light in an oven with a maximum UV output of about 300-400 nm.
[0016] In one embodiment, a release liner may be attached to the oil-resistant OCA before use. Any suitable release liner may be used without departing from the intended scope of the present invention. Exemplary release liners include those prepared from paper (e.g., kraft paper) or polymeric materials (e.g., polyolefins such as polyethylene or polypropylene, ethylene vinyl acetate, polyurethane, and polyesters such as polyethylene terephthalate). At least some release liners are coated with a layer of a release agent, such as a silicone-containing material or a fluorocarbon-containing material. Exemplary release liners include, but are not limited to, liners available from SKC Haas (Rochester, NY) under the trade names "RF02N" and "RF12N", which have a silicone release coating on a polyethylene terephthalate (PET) film.
[0017] During use, the release liner is removed to allow the oil-resistant OCA to adhere to another substrate (i.e., removal of the release liner exposes a surface of the adhesive layer that can later be bonded to another substrate surface). In many cases, the oil-resistant OCA will be permanently bonded to this other substrate, but in some cases, the adhesion may be limited to allow for rework of the display.
[0018] The optically clear adhesive of the present invention has high oil resistance performance. High oil resistance performance means that the OCA maintains optical clarity, bond strength, and resistance to delamination (e.g., swelling) over the life of the article in which it is used. As used herein, the term "optically clear" refers to a material that, when cured, has a haze of less than about 6%, particularly less than about 4%, more particularly less than 2%, and most particularly less than about 1%, a light transmittance of greater than about 88%, particularly greater than about 89%, more particularly greater than about 90%, and an optical transparency of greater than about 98%, particularly greater than about 99%, more particularly greater than about 99.5%. Typically, the transparency, haze, and transmittance are measured on a structure in which the adhesive is held between two optical films, such as poly(ethylene terephthalate), PET. Measurements are then taken on the entire structure, including the adhesive and the substrate. Both the haze and light transmittance can be measured, for example, using ASTM-D 1003-92. Optical measurements of transmittance, haze, and optical clarity can be performed, for example, using a BYK Gardner haze-gard plus 4725 instrument (Geretsried, Germany). The BYK instrument uses an illuminant "C" source and measures all light across its spectral range to calculate the transmission value. Haze is the percentage of transmitted light that deviates from the incident beam by more than 2.5°. Optical clarity is evaluated at angles of less than 2.5°. Typically, the grease-resistant OCA is visually bubble-free. In one embodiment, the grease-resistant OCA maintains these optical properties even after being immersed in oleic acid at room temperature and in a 70°C oven for 4 hours, removed, left to stand for about 5 minutes, and then measured.
[0019] When an adhesive swells in contact with oil, it can become "gelled" and lead to cohesive failure, weakening the mechanical strength of the adhesive, and causing haze, bubbles, delamination, and / or excessive swelling (which can lead to bondline distortion). The oil-resistant OCA of the present invention shows minimal to no swelling when in contact with oil. In one embodiment, after immersion in either oleic acid or oleic acid and oleic acid / olive oil mixture (40 / 60) at room temperature for 7 days or after accelerated aging in an oven at 70°C for 4 hours, the oil-resistant OCA of the present invention shows no noticeable swelling. One way to measure swelling is to measure the percentage swelling of the adhesive after immersion in either oleic acid or oleic acid and oleic acid / olive oil mixture (40 / 60) at room temperature for 7 days or after accelerated aging in an oven at 70°C for 4 hours. The percentage swelling is defined as the change in length / original length of the OCA. In one embodiment, the oil resistant OCA has a percent expansion of less than about 10%, specifically less than about 5%, and most specifically less than about 3%.
[0020] In order for the adhesive to swell, the oil must have some degree of solubility in all or at least a portion of the adhesive. The oil-resistant OCA of the present invention has a solubility parameter that minimizes or prevents swelling. The total solubility parameter of an adhesive provides an idea of the strength of the interactions between molecules in a compound and is a good indicator of the solubility of a composition. The hydrogen bond solubility parameter specifically gives an idea of the strength of the so-called hydrogen bond interactions. The total solubility parameter is defined as the square root of the molecular interaction energy (called the cohesive energy) divided by the volume. In one embodiment, the oil-resistant OCA has a solubility parameter of about 9.9 to about 14 (cal / cm 3 ) 1 / 2 In some embodiments, the total solubility parameter is about 13, about 12.5, about 12, about 11.5, or about 11 (cal / cm 3 ) 1 / 2 In one embodiment, the oil-resistant OCA has a viscosity of about 4.9 to about 7 (cal / cm 3 ) 1 / 2In some embodiments, the hydrogen bond solubility parameter is about 6.5 or 6.0 (cal / cm 3 ) 1 / 2 The following is the result.
[0021] The oil-resistant OCA also has a rheology that promotes good adhesion. In one embodiment, the oil-resistant OCA of the present invention has a post-cure glass transition temperature of about -25°C to about 10°C, particularly about -25°C to about 0°C, more particularly about -20°C to about -5°C. In one embodiment, the tan δ of the oil-resistant OCA at 70°C, which is a measure of the flowability of the OCA at high temperatures, is greater than about 0.5. Thus, the oil-resistant OCA can flow on and around surfaces with various topographies. Thus, the oil-resistant OCA can be applied to an ink step on a substrate such as, for example, glass. The elastic modulus and glass transition temperature of the oil-resistant OCA can be measured using a rheological dynamic analyzer, such as, for example, a model DHR-3 rheometer available from TA Instruments (New Castle, Del., USA).
[0022] The oil-resistant OCA of the present invention also has effective adhesion even though it is resistant to oil. In one embodiment, when removed after conditioning at room temperature and 50% relative humidity (RH) for 24 hours, the oil-resistant OCA has an adhesion of more than about 3 N / cm, particularly more than about 5 N / cm, particularly more than about 10 N / cm, using a crosshead speed of 12 inches / min at an angle of 180 degrees. Peel adhesion strength can be evaluated, for example, using an IMASS SP-2100 tester (available from IMASS INC., Accord, MA). If the peel adhesion of the oil-resistant OCA is too low, the adhesive may break and the article containing it may fall apart (delaminate). For example, the adhesive may be considered to have broken if adhesive residue remains on either one or both substrates positioned adjacent to one side of the adhesive. EXAMPLES
[0023] The present invention is described in more detail in the following examples, which are for purposes of illustration only, since numerous modifications and variations within the scope of the invention will become apparent to those skilled in the art. Unless otherwise noted, all parts, percentages and ratios reported in the following examples are by weight.
[0024] [Table 1]
[0025] Test Method Oil resistance test: Optically clear adhesive (OCA) samples were made by slitting and cutting 0.5 inch by 0.5 inch (1.27 cm by 1.27 cm) test strips from each of the prepared adhesive transfer tape samples. The release liner on one side of the sample was then removed and the square sample of OCA was fixed (bonded) to the bottom surface of a Petri dish. The top liner was also removed to expose the surface of the OCA, and the Petri dish with the fixed sample was left at room temperature (RT, approximately 23° C.) for 15 minutes. The OCA samples were either immersed in oleic acid or oleic acid / olive oil (40 / 60) at room temperature for one week or aged in a 70° C. oven for four hours. The resistance of the adhesive samples to oleic acid was evaluated and reported using the following guidelines: Samples were rated as "5" if no swelling, discoloration or bubbles occurred, "3" if haze occurred around the edge areas or in the bulk of the sample, and "1" if swelling, discoloration and bubbles were observed in the sample.
[0026] A. Expansion test The expansion test measures the (XY) dimensional change of a sample after it is immersed in oil and aged at room temperature for 7 days. The expansion is defined as the change in length of the OCA sample / original length. For example, if the original length of the OCA is 1.27 cm and after 7 days of chemical immersion, the length becomes 1.5 cm, the expansion is 0.23 / 1.27 * 100=18.1%. The OCA preferably has a swelling percentage of less than about 10%, less than about 5%, or less than about 3%.
[0027] B. Haze test The haze test measures whether a sample becomes cloudy in bulk after immersion in oil. After making 2" x 4" OCA sample strips, the Easy Liner (RF02N) was removed. The top side of the OCA sample was clamped with a binder clip and then the bottom half of the sample was immersed in oleic acid. The sample was then aged at 70°C for 4 hours. The sample was removed from the liquid and allowed to sit for 5 minutes before measuring the haze of the sample using a Haze-Guard Plus Haze Meter (commercially available from BYK-Gardner, Columbia, MD).
[0028] Initial peel adhesion strength test Adhesive tape sample test strips were made by removing the easy liner, typically RF02N, laminating a 2 mil (50 micrometer) primed PET film onto the adhesive, then slitting and cutting long test strips 12.7 mm wide. Two replicates were prepared for each adhesive type / panel. After removing the cling liner, the exposed adhesive surface was then adhered along the length of a float glass substrate and rolled twice. After conditioning at room temperature and 50% relative humidity (%RH) for 24 hours. Peel adhesion strength was evaluated using an IMASS SP-2100 tester (available from IMASS INC. Accord, MA) using a crosshead speed of 12 inches / minute at an angle of 180° and reported in units of [N / cm].
[0029] Shear storage modulus and glass transition temperature (Tg) The elastic modulus and glass transition temperature (Tg) of the adhesive samples were measured using a rheology dynamic analyzer (Model DHR-3 rheometer available from TA Instruments, New Castle, Del., USA) in parallel plate mode. OCA samples were made by laminating OCA layers to a thickness of approximately 1 millimeter (0.039 inches). Samples were then punched using a circular die with a diameter of 8 millimeters (0.315 inches) and, after removal of the release liner, were centered between two parallel plates, each with a diameter of 8 millimeters. The plate with the adhesive was positioned in the rheometer and compressed until the edges of the adhesive film were even with the edges of the upper and lower plates. The parallel plates were then oscillated at an angular frequency of 1 rad / sec and a constant strain of 10%, while the temperature was ramped in two steps, first from 25°C to -65°C at 3°C / min, and then from 25°C to 150°C at 3°C / min, after equilibrating back to 25°C. The shear storage modulus (G') and shear loss modulus (G") were measured and used to calculate tan δ as a function of temperature (TD=G" / G'). The peak of the tan δ curve was taken as the glass transition temperature.
[0030] Solubility parameter The homopolymer solubility parameters were calculated using the group contribution method as described in DW van Krevelen, Properties Of Polymers, 3rd ed., 1990, Elsevier. The calculations were performed using the Molecular Modeling Pro Plus program from Norgwyn Montgomery Software, Inc. (North Wales, Pa.). The copolymer solubility parameters were then calculated as a volume fraction weighted average of the homopolymer solubility parameters.
[0031] Working Example The monomer premixes of Examples 1-3 were prepared according to the weight ratios listed in Table 1 and partially polymerized by exposure to UV light in a nitrogen atmosphere to form coatable syrups with a viscosity of approximately 1000 cp. To each syrup, an additional 0.25% by weight of Irgacure 651 was added and the syrups were mixed on a roller overnight. The resulting syrups were degassed and knife coated between two siliconized release liners (RF02N and RF12N) at a thickness of 150 microns. The resulting coatings were then baked in an oven with a maximum spectral output of 300-400 nm (total energy 1920 mJ / cm). 2 ) and exposed to low intensity UV light. The cured OCA sheets were collected.
[0032] [Table 2]
[0033] The results of the oil resistance test for Examples 1 to 3 are shown in Table 2.
[0034] [Table 3]
[0035] The monomer premixes of Examples 4-5 were prepared according to the weight ratios listed in Table 3 and partially polymerized by exposure to UV light in a nitrogen atmosphere to form coatable syrups with a viscosity of approximately 1000 cp. To each syrup, 0.25% by weight of Irgacure 651 and 0.08% HDDA were added and the syrups were mixed on a roller overnight. The resulting syrups were degassed and knife coated between two siliconized release liners (RF02N and RF12N) at a thickness of 150 microns. The resulting coatings were then baked in an oven with a maximum spectral output of 300-400 nm (total energy 1920 mJ / cm). 2 ) and exposed to low intensity UV light. The cured OCA sheets were collected.
[0036] [Table 4]
[0037] The results of the oil resistance test for Examples 4 and 5 are shown in Table 4.
[0038] [Table 5]
[0039] The monomer premixes of Examples 6-10 were prepared according to the weight ratios listed in Table 5 and partially polymerized by exposure to UV light in a nitrogen atmosphere to form coatable syrups with a viscosity of approximately 1000 cp. To each syrup, 0.25% by weight of Irgacure 651 was added and the syrups were mixed on a roller overnight. The resulting syrups were degassed and knife coated between two siliconized release liners at a thickness of 150 microns. The resulting coatings were then baked in an oven with a maximum spectral output of 300-400 nm (total energy 1920 mJ / cm). 2 ) and exposed to low intensity UV light. The cured OCA sheets were collected.
[0040] [Table 6]
[0041] According to the oil resistance evaluation, all of the formulations of Examples 6-9 were rated as 5. Rheology, peel adhesion, and expansion tests were also performed on Examples 6-9 and CE6. The results are shown in Table 6.
[0042] [Table 7]
[0043] The calculated solubility parameters for Examples 6-11 were also measured and are listed in Table 7.
[0044] [Table 8]
[0045] Table 8 shows the results of the oil resistance test for Examples 10 to 12 and CE6.
[0046] [Table 9]
[0047] While specific embodiments of the present invention have been shown and described herein, it will be understood that these embodiments are merely illustrative of the many possible specific configurations that may be devised by applying the principles of the present invention. Those skilled in the art will be able to devise numerous and varied other configurations in accordance with these principles without departing from the spirit and scope of the present invention. Thus, the scope of the present invention should not be limited to the structures described herein, but only by the structures described by the language of the claims and the equivalents of such structures. The present invention includes the following aspects. (1) a hydroxyalkyl (meth)acrylate having an alkyl group containing 2 to 4 carbon atoms; a short alkyl (meth)acrylate having an alkyl group containing 6 or fewer carbons; A photoinitiator; wherein after immersion of the adhesive composition in oleic acid at room temperature for 7 days, the adhesive composition has a swelling percentage of less than about 10%. (2) The oil-resistant adhesive composition according to item 1, wherein the hydroxyalkyl (meth)acrylate having an alkyl group containing 2 to 4 carbons comprises one of 4-hydroxybutyl acrylate (4-HBA) and 2-hydroxyethyl acrylate (2-HEA). (3) The oil-resistant adhesive composition according to item 1, wherein the short alkyl (meth)acrylate having an alkyl group containing 6 or less carbons comprises one of n-hexyl acrylate, n-butyl acrylate, cyclohexyl methacrylate (CHMA), cyclohexyl acrylate (CHA), and 2-methylbutyl acrylate. (4) The oil-resistant adhesive composition according to item 1, wherein the oil-resistant adhesive composition is optically transparent. (5) The oil-resistant adhesive composition according to item 1, wherein the oil-resistant adhesive composition has a haze of less than about 5% after being immersed in oleic acid at room temperature and placed in an oven at 70° C. for 4 hours, then removed from the oleic acid and allowed to stand for about 5 minutes. (6) The oil-resistant adhesive composition has a viscosity of about 9.9 to about 14 (cal / cm 3 ) 1 / 2 2. The oil-resistant adhesive composition according to item 1, having a total solubility parameter of (7) The oil-resistant adhesive composition has a viscosity of about 4.9 to about 7 (cal / cm 3 ) 1 / 2 2. The oil-resistant adhesive composition according to item 1, having a hydrogen bond solubility parameter of (8) The oil-resistant adhesive composition according to item 1, wherein the oil-resistant adhesive composition has a post-cure glass transition temperature of about -25°C to about 10°C. (9) The oil-resistant adhesive composition according to item 1, wherein the oil-resistant adhesive composition has an adhesion of greater than about 3 N / cm using a crosshead speed of 12 in / min at an angle of 180 degrees. (10) The oil-resistant adhesive composition according to item 1, further comprising a chain transfer agent. (11) The oil-resistant adhesive composition according to item 1, wherein the oil-resistant adhesive composition comprises at least about 35% by weight of a hydroxyalkyl (meth)acrylate having an alkyl group containing 2 to 4 carbons. (12) at least about 35% by weight of a hydroxyalkyl (meth)acrylate having an alkyl group containing 2 to 4 carbons; a short alkyl (meth)acrylate having an alkyl group containing 6 or fewer carbons; A photoinitiator; wherein the oil-resistant adhesive composition has a haze of less than about 5% after being immersed in oleic acid at room temperature and placed in an oven at 70° C. for 4 hours, then removed from the oleic acid and allowed to stand for about 5 minutes. (13) The optically transparent oil-resistant adhesive composition according to item 12, wherein the hydroxyalkyl (meth)acrylate having an alkyl group containing 2 to 4 carbons comprises one of 4-hydroxybutyl acrylate (4-HBA) and 2-hydroxyethyl acrylate (2-HEA). (14) The optically clear oil-resistant adhesive composition according to item 12, wherein the short alkyl (meth)acrylate having an alkyl group containing 6 or less carbons comprises one of n-hexyl acrylate, n-butyl acrylate, cyclohexyl methacrylate (CHMA), cyclohexyl acrylate (CHA), and 2-methylbutyl acrylate. (15) The oil-resistant adhesive composition has a viscosity of about 9.9 to about 14 (cal / cm 3 ) 1 / 2 Item 13. The optically clear oil-resistant adhesive composition according to item 12, having a total solubility parameter of (16) The oil-resistant adhesive composition has a viscosity of about 4.9 to about 7 (cal / cm 3 ) 1 / 2 13. The optically clear oil resistant adhesive composition according to item 12, having a hydrogen bond solubility parameter of (17) The optically transparent oil-resistant adhesive composition according to item 12, wherein the oil-resistant adhesive composition has a post-cure glass transition temperature of about -25°C to about 10°C. (18) The optically clear oil-resistant adhesive composition according to item 12, wherein the adhesive composition has a swelling percentage of less than about 10% after immersion of the adhesive composition in oleic acid at room temperature for 7 days. (19) The optically clear oil-resistant adhesive composition according to item 12, wherein the oil-resistant adhesive composition has an adhesion of greater than about 3 N / cm using a crosshead speed of 12 in / min at an angle of 180 degrees. (20) The optically clear, oil-resistant adhesive composition according to item 12, further comprising a chain transfer agent.
Claims
1. 40% to 80% by weight of a hydroxyalkyl (meth)acrylate having an alkyl group containing 2 to 4 carbons; a short alkyl (meth)acrylate having an alkyl group containing 6 or fewer carbons; Optionally, a monomer selected from 2-ethoxyethoxyethyl acrylate, acrylamide, 2-cyanoethyl acrylate, and tetrahydrofurfuryl acrylate; A photoinitiator; A polymerizable composition for preparing an oil-resistant adhesive, comprising: A polymerizable composition, wherein an oil-resistant adhesive prepared using the polymerizable composition has a swelling percentage of less than 10% after immersion in oleic acid at room temperature for 7 days.
2. 2. The polymerizable composition of claim 1, wherein the hydroxyalkyl (meth)acrylate having an alkyl group containing 2 to 4 carbons comprises one of 4-hydroxybutyl acrylate (4-HBA), 2-hydroxyethyl acrylate (2-HEA).
3. 2. The polymerizable composition of claim 1, wherein the short alkyl (meth)acrylate having an alkyl group containing 6 or fewer carbons comprises one of n-hexyl acrylate, n-butyl acrylate, cyclohexyl methacrylate (CHMA), cyclohexyl acrylate (CHA), and 2-methylbutyl acrylate.
4. The polymerizable composition of claim 1 , wherein the oil-resistant adhesive is optically clear.
5. 2. The polymerizable composition of claim 1, wherein the oil-resistant adhesive has a haze of less than 5% after being immersed in oleic acid at room temperature for 4 hours in a 70° C. oven, removed from the oleic acid, and allowed to stand for 5 minutes, the haze being measured using ASTM-D1003-92.
6. The oil-resistant adhesive has a viscosity of 9.9 to 14 (cal / cm 3 ) 1/2 The polymerizable composition of claim 1 having a total solubility parameter of
7. The oil-resistant adhesive has a viscosity of 4.9 to 7 (cal / cm 3 ) 1/2 The polymerizable composition of claim 1 having a hydrogen bond solubility parameter of
8. 2. The polymerizable composition of claim 1, wherein the oil-resistant adhesive has a glass transition temperature after curing of from -25°C to 10°C.
9. 10. The polymerizable composition of claim 1, wherein the oil resistant adhesive has an adhesion of greater than 3 N / cm using a crosshead speed of 12 in / min at an angle of 180 degrees.
10. The polymerizable composition of claim 1 further comprising a chain transfer agent.
Citation Information
Patent Citations
Adhesive, adhesive layer, and adhesive sheet
JP2014034655A
Optically transparent adhesive and optical laminate
JP2016050239A
Adhesive composition
JP2017008299A
Optically Clear Adhesive for Bonding Durable Plastics
JP2017507193A